Association between cheese and fish consumption and the occurrence of depression based on European population: mediating role of metabolites - Chen, Yan; Lin, Jixin; Tao, Ming (Frontiers in Nutrition, 2024)
Background: The connection between consuming cheese, consuming fish, experiencing depression, and the pathways that mediate this relationship remains unclear. The purpose of this research is to investigate the potential association between the consumption of cheese and fish and the occurrence of depression. Moreover, it is important to identify any metabolites that might be involved and understand their respective roles and functions. Methods: A two-step, two-sample Mendelian randomization (MR) study was conducted using genome-wide association study data on cheese, non-oily fish, and oily fish consumption and depression, along with 12 alternate mediators. Results: The data we collected suggested that consuming more cheese correlated with a lower likelihood of experiencing depression. Neither non-oily fish nor oily fish consumption were directly linked to depression onset. Although there was a direct causal relationship with depression, the mediating relationship of triglycerides, total cholesterol in large HDL, cholesterol to total lipids ratio in large HDL, free cholesterol to total lipids ratio in large HDL, glycine, phospholipids to total lipids ratio in very large HDL of cheese intake on depression risk were -0.002 (95% CI: -0.023 - 0.020), -0.002 (95% CI: -0.049 - 0.045), -0.001 (95% CI: -0.033 - 0.031), -0.001 (95% CI: -0.018 - 0.015), 0.001 (95% CI: -0.035 - 0.037), -0.001 (95% CI: -0.024 - 0.021), respectively. The mediating relationship of uridine, free cholesterol to total lipids ratio in large HDL, total cholesterol in large HDL, acetoacetate and 3-hydroxybutyrate between non-oily fish consumption and depression risk were 0.016 (95% CI: -0.008 - 0.040), 0.011 (95% CI: -1.269 - 1.290), 0.010 (95% CI: -1.316 - 1.335), 0.011 (95% CI: -0.089 - 0.110) and 0.008 (95% CI: -0.051 - 0.068), respectively. The mediation effect of uridine and free cholesterol to total lipids ratio in large HDL between intake of oily fish and the risk of depression were found to be 0.006 (95% CI: -0.015 - 0.028) and -0.002 (95% CI: -0.020 - 0.017), respectively. Conclusions: The consumption of cheese and fish influenced the likelihood of experiencing depression, and this may be mediated by certain metabolites in the body.